MOTIF DAN KEPUASAN MENONTON VIDEO BLOG DI KALANGAN ANAK MUDA KOTA DENPASAR - Baracha Kaban, Silya Christine; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium; Vol 1 No 2 (2018), 2018)
ABSTRACT Vlogs are a form of opinion video, and are the dominant video in YouTube that is as much as 40% of all video content types that exist on YouTube. The presence of vlog is quite welcomed by the people of Indonesia, as seen from the number of Indonesian YouTubers already have a vlog-based account. Vlogs are composed with various types of content. The use of a media is influenced by individual socio-psychological factor that is one of the motive. This study aims to find out what the motive and how the satisfaction of young people in the city of Denpasar in watching vlog. Denpasar city was choosen to be the subject of this research because Denpasar city is listed as the most widely used internet in the Province of Bali. The motive of consuming the media became the reference in this research is the motive proposed by Dennis McQuail. The theory that is used in this research is Uses and Gratifications Theory. This research uses descriptive quanitative method. Sampling technique in this research is a purposive sampling. Data were obtained by distributing questionnaires using Likert scale. The analytical technique used is descriptive statistics by looking at the mean score of motives and satisfaction. The results showed that there are two motives that can be satisfied in watching the vlog that is the motif of personal identity and integrity and social interaction. Motives that can not be satisfied in watching the vlog is the motive of information and the motive of entertainment. So the results of this research indicate that vlog can be said as an effective media because it can provide some satisfaction to the audience. Keyword: Denpasar, Motive, Satisfaction, Vlog, Young People